Influence of prey depletion and human disturbance on tiger occupancy in Nepal. (21st August 2012) - Barber‐Meyer, S. M.; Jnawali, S. R.; Karki, J. B.; Khanal, P.; Lohani, S.; Long, B.; MacKenzie, D. I.; Pandav, B.; Pradhan, N. M. B.; Shrestha, R.; Subedi, N.; Thapa, G.; et al.
Abstract Tigers are globally endangered and continue to decline due to poaching, prey depletion and habitat loss. In Nepal, tiger populations are fragmented and found mainly in four protected areas (PAs). To establish the use of standard methods, to assess the importance of prey availability and human disturbance on tiger presence and to assess tiger occupancy both inside and outside PAs, we conducted a tiger occupancy survey throughout the Terai Arc Landscape of Nepal. Our model‐average estimate of the probability of tiger site occupancy was 0.366 [standard error (se) = 0.02, a 7% increase from the naive estimate] and the probability of detection estimate was 0.65 (se = 0.08) per 1 km searched. Modeled tiger site occupancy ranged from 0.04 (se = 0.05) in areas with a relatively lower prey base and higher human disturbance to 1 (se = 0 and 0.14) in areas with a higher prey base and lower human disturbance. We estimated tigers occupied just 5049 (se = 3) km2 (36%) of 13 915 km2 potential tiger habitat (forests and grasslands), and we detected sign in four of five key corridors linking PAs across Nepal and India, respectively indicating significant unoccupied areas likely suitable for tigers and substantial potential for tiger dispersal. To increase tiger populations and to promote long‐term persistence in Nepal, otherwise suitable areas should be managed to increase prey and minimize human disturbance especially in critical corridors linking core tiger populations.